Improved quality of life with immediate versus deferred initiation of antiretroviral therapy in early asymptomatic HIV infection. (24th April 2017) - Lifson, Alan R.; Grund, Birgit; Gardner, Edward M.; Kaplan, Richard; Denning, Eileen; Engen, Nicole; Carey, Catherine L.; Chen, Fabian; Dao, Sounkalo; Florence, Eric; Sanz, Jesus; Emery, Sean
Abstract : Objective: To determine if immediate compared to deferred initiation of antiretroviral therapy (ART) in healthy persons living with HIV had a more favorable impact on health-related quality of life (QOL), or self-assessed physical, mental, and overall health status. Design: QOL was measured in the Strategic Timing of Antiretroviral Therapy study, which randomized healthy ART-naive persons living with HIV with CD4 + cell counts above 500 cells/μl from 35 countries to immediate versus deferred ART. Methods: At baseline, months 4 and 12, then annually, participants completed a visual analog scale (VAS) for 'perceived current health' and the Short-Form 12-Item Health Survey version 2 from which the following were computed: general health perception; physical component summary (PCS); and mental component summary (MCS); the VAS and general health were rated from 0 (lowest) to 100 (highest). Results: QOL at study entry was high (mean scores: VAS = 80.9, general health = 72.5, PCS = 53.7, MCS = 48.2). Over a mean follow-up of 3 years, changes in all QOL measures favored the immediate group ( P  < 0.001); estimated differences were as follows: VAS = 1.9, general health = 3.6, PCS = 0.8, MCS = 0.9. When QOL changes were assessed across various demographic and clinical subgroups, treatment differences continued to favor the immediate group. QOL was poorer in those experiencing primary outcomes; however, when excluding those with primary events, results remained favorable for immediate ART recipients. Conclusion: In an international randomized trial in ART-naive participants with above 500 CD4 + cells/μl, there were modest but significant improvements in self-assessed QOL among those initiating ART immediately compared to deferring treatment, supporting patient-perceived health benefits of initiating ART as soon as possible after an HIV diagnosis. Abstract : Supplemental Digital Content is available in the text